The Relationships among Cryptocurrencies: A Granger Causality Analysis - Khan, Nadir; Durrani, Muhammad Zohair; Mushtaq, Naila; Haq, S M Nabeel ul; Ijaz, Babar (iRASD Journal of Economics, 2022)
The topic of Cryptocurrencies is emerging rapidly. Many investors and public want to invest in digital currencies. So, the nature of cryptocurrency and its theoretical understanding is essential currently. The aim of this research is to study major Cryptocurrencies having capitalization above 1bn and construct directed networks. Eleven major Cryptocurrencies are Bitcoin (BTC), Ethereum (ETH), Cardano (ADA), Binance Coin (BNB), Tether (USDT), Ripple (XRP), Doge Coin (DOGE), USD Coin (USDC), Bitcoin Cash (BCH), Chainlink (Link) and Litecoin (LTC). By using returns Granger Causality test was conducted. This test help in concluding that whether change in one price of cryptocurrency cause a change in other Cryptocurrencies or not. After analysis of results, it was concluded that there is a variation in the Cryptocurrencies relation. Some shows a direct cause and effect relation, while some have a unidirectional relation. However, some of them also showed no meaningful relationship. The relationship among these Cryptocurrencies was then showed using directed networks.